THE EFFECT OF COVID-19 PHOBIA ON THE SATISFACTION WITH LIFE AND FAMILY SENSE OF BELONGING LEVELS OF MIDWIFERY STUDENTS - Altiparmak, Sumeyye; Yilmaz, Ayse Nur; Derya, Yesim A. K. S. O. Y. (Dokuz Eylul Univ Inst Health Sciences, 2021)
Purpose: This research was conducted with the purpose of determining the impact of COVID-19 phobia on the satisfaction with life and family sense of belonging levels of midwifery students. Methods: Sample of this cross-sectional research consisted of 484 students studying at Midwifery Departments of two universities located in the eastern of Turkey. The data was collected with Personal Information Form, Satisfaction with Life Scale, Family Sense of Belonging Scale and Coronavirus 19 Phobia Scale. Average, standard deviation, percentage distribution and Pearson Correlation Analysis were used in the statistical assessment. Results: The average score that midwifery students get from Satisfaction with Life Scale was found as 13.54 +/- 4.37, their average score from Family Sense of Belonging Scale was found as 64.59 +/- 13.29 and average score from Coronavirus 19 Phobia Scale was found as 50.02 +/- 17.36.It was determined that Family Sense of Belonging Scale total and all sub-dimension average scores increased significantly as the Coronavirus 19 Phobia Scale Psychological Phobia sub-dimension average score increases (p<0.05). In addition, it was determined that Family Sense of Belonging Scale Family Sense of Belonging sub dimension average score increased significantly as the Coronavirus 19 Phobia Scale Social Phobia sub dimension average score increases (p<0.05). However, it was determined that Satisfaction with Life decreased significantly as Coronavirus 19 Phobia Scale Psychosomatic Phobia and Economic Phobia sub-dimension average scores increase (p<0.05). Conclusions: It was determined that midwifery students have moderate level of COVID-19 phobia and psychological and social phobia levels regarding COVID-19 increase family sense of belonging, but psychosomatic and economic phobia levels decrease satisfaction with life.
Keywords: COVID-19 phobia; family belonging; midwifery students; satisfaction with life